Pengaruh Likuiditas, Leverage, Dan Good Corporate Governance Terhadap Financial Distress pada Perusahaan Manufaktur Pertambangan Tahun 2015-2019 - lucki nur handayani (Journal Of Business, Finance, and Economics (JBFE), 2021)
This study aims to analyze the effect of liquidity, leverage, and good corporate governance on the financial distress condition of manufacturing companies. Financial distress is measured by the interest coverage ratio, a ratio smaller than 1 in the financial distress category. the liquidity ratio in this study is measured by the current ratio, the leverage ratio is measured by total debt to total equity, institutional ownership is measured by institutional ownership of shares, and independent commissioners are measured by the number of independent commissioners. The population in this study are manufacturing companies in the mining sector in 2015-2019. The sampling technique used was purposive sampling, the sample used in this study were 110 companies consisting of 58 companies categorized as financial distress and 52 not experiencing financial distress. The data analysis technique for non-financial difficulties used logistic regression analysis with dummy cariables. The results showed that the liquidity ratio had no significant effect, the leverage ratio had a significant effect, institutional ownership had no significant effect, and independent commissioners had no significant effect on financial distress. It is advisable for company managers to pay attention to the factors that affect financial distress in order to overcome these problems early. For further researchers, it is expected to add several other variables that are thought to have an effect on financial distress and it is recommended that other research objects be selected, in order to expand the object of research so that they are able to generalize the results of research studies and use types of measurement of financial distress other than the interest coverage ratio (ICR). Key Words: likuiditas, leverage, kepemilikkan institusional, komisaris, dan financial distress